FRI0117 Analysis of risk for cardiovascular events and assessment of diagnostic and therapeutic management of patients with rheumatoid arthritis in clinical practice: the epidauro registry. (23rd January 2014) - Viapiana, O.; Faden, G.; Fischetti, F.; Cioffi, G.; Rossini, M.; Caimmi, C.; Faggiano, P.; Gatti, D.; Faganello, G.; Di Lenarda, A.; Filippini, M.; Adami, S.; et al.
Abstract : Background: A number of studies have clearly documented a higher mortality rate in patients with rheumatoid arthritis (RA) than in general population, comparable to that found in patients with type 2 diabetes mellitus, mainly due to cardiovascular (CV) causes. No improvement in CV mortality over the last 50 years has been observed in recent meta-analyses in RA patients. Objectives: The " EPIDAURO registry" (Registro sull' EPIdemiologia Dell'Artrite reUmatoide e Rischio cardiOvascolare) collected information on the risk of CV events and on the clinical management (diagnostic tests and therapy for CV risk factors control) of RA patients to highlight possible reasons for lacking of reduction in CV mortality over time in these patients. Methods: Anamnestic and clinical data of 721 patients with RA followed by 4 Italian Centers were retrospectively analyzed. The CV risk was graded according to the score of European Society of Cardiology. Subjects with a probability > 5% of CV events in the following 10 years were considered at increased CV risk. No exclusion criterion was considered for inclusion into the registry. Results: Study patients had a mean age of 61±14 years, 29% was male, mean duration of AR was 11±8 years. The mean number of joints implicated was 5 per patient; the state of activity of the disease was high in 18% of patients. Hypertension coexisted in 48% of cases, dyslipidemia in 62%, diabetes 11%, smokers were 23%, known coronary artery disease 6%, previous myocardial infarction or heart failure 5% and 3%, respectively. 396 patients had multiple risk factors and were considered at increased risk independent of RA. Interestingly, information on physical activity was available in 40% of participants, waist circumference was measured in 41% of them and in only 39% were available all parameters allowing diagnosis of metabolic syndrome, serum vitamin D levels were measured in 19% (mean 27±5 ng/ml). Considering the diagnostic tests, an ECG was performed in 65% of patients, echocardiogram in 29%, exercise stress test in 6%, carotid ultrasound imaging in 13%, automatic 24 hours blood pressure or ECG monitoring in 19% and 9% respectively. In regards to the pharmacological therapy, beta-blockers were prescribed in 20% of patients, ACEi/ARBs in 30%, antiplatelet agents in 21% and statins in 20%. In patients who had an increased CV risk, echocardiography and exercise stress test were performed more frequently (36 vs 20% and 9 vs 4%, respectively; all p < 0.01) and beta-blockers and ACEi/ARBs were prescribed more commonly (27 vs 14% and 45 vs 11%, respectively, all p < 0.01) than patients who had not. Conclusions: An increased CV risk is present in more than half of patients with RA examined in daily clinical practice . In these patients the available information essential for a complete CV evaluation including the presence of inducible myocardial ischemia and prognostic assessment are lacking in the vast majority of subjects and pharmacological treatment for managing CV risk factors is sub-optimal. Disclosure of Interest: None Declared